2015
DOI: 10.1016/j.ajp.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Illness beliefs of Chinese American immigrants with major depressive disorder in a primary care setting

Abstract: Underutilization of mental health services in the U.S. is compounded among racial/ethnic minorities, especially Chinese Americans. Culturally based illness beliefs influence help-seeking behavior and may provide insights into strategies for increasing utilization rates among vulnerable populations. This is the first large descriptive study of depressed Chinese American immigrant patients’ illness beliefs using a standardized instrument. 190 depressed Chinese immigrants seeking primary care at South Cove Commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Subjects of MDD in our sample showed a mean stigma score of 17 ± 9, basically consistent with the mean score of 16 ± 8 observed in an earlier study (Chen et al, ) evaluating the EMIC stigma scores in 190 depressed Chinese American immigrants and the mean stigma score of 19.7 ± 7.2 in another study (Chowdhury et al, ) conducted in MDD patients in India. Together, these studies suggest a high stigma level in Asian MDD populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Subjects of MDD in our sample showed a mean stigma score of 17 ± 9, basically consistent with the mean score of 16 ± 8 observed in an earlier study (Chen et al, ) evaluating the EMIC stigma scores in 190 depressed Chinese American immigrants and the mean stigma score of 19.7 ± 7.2 in another study (Chowdhury et al, ) conducted in MDD patients in India. Together, these studies suggest a high stigma level in Asian MDD populations.…”
Section: Discussionsupporting
confidence: 92%
“…The EMIC has been confirmed to have good validation and reliability for the investigation of stigma in cross-cultural applicability, as shown in the studies of onchocerciasis in Nigeria (Brieger, Oshiname, & Ososanya, 1998), MDD (Chowdhury et al, 2001), leprosy (Van Brakel et al, 2012), and mental health and HIV (Stevelink, Van Brakel, & Augustine, 2011) in India. A study (Chen, Hung, Parkin, Fava, & Yeung, 2015) had applied EMIC to examine the illness beliefs of MDD patients among Chinese American immigrants. These patients showed a high stigma level; nearly half of them reported they would conceal the name of their problem from others.…”
mentioning
confidence: 99%
“…Mental illness, such as depression, is said to be influenced by illness beliefs formed based on cultural and individual values (Chen, Hung, Parkin, Fava, & Yeung, ; Juhasz, Eszlari, Pap, & Gonda, ; Syrén & Hultsjö, ). Illness beliefs bolster disease and distress (Wright & Bell, ).…”
Section: Depression‐linked Beliefs In Older Adults With Depressionmentioning
confidence: 99%
“…In various studies, schizophrenia was perceived as the more severe mental disorder [ 51 – 53 ] followed by alcohol abuse, anxiety disorders and lastly depression, a perceived hierarchy that persists also in the Vietnamese context [ 22 ]. Contrasting to schizophrenia, causes of depression, especially in the Asian cultural sphere, were perceived as being rooted in psychosocial or interpersonal related stressors rather than in biochemical dysbalances, [ 22 , 54 56 ], thus interpersonal treatment providers were more often favoured. These differences between causal beliefs about schizophrenia and depression could also account for the substantial difference in recommendation between schizophrenia and depression for psychiatrists in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, self-help strategies and person of trust were recommended more frequently for the depression than for the schizophrenia vignette. Chen and colleagues [ 54 ] reported that 75% of Asian American participants with depression endorsed self-management as favorable over pharmacological interventions. The authors also embedded the findings in the understanding of the etiology of depression as being of psychosocial rather than biochemical origin [ 54 ].…”
Section: Discussionmentioning
confidence: 99%